Invasive pulmonale Aspergillose - Matthews, Hanna; Rohde, Holger; Wichmann, Dominic; Kluge, Stefan (DMW - Deutsche Medizinische Wochenschrift, 2019)
Invasive pulmonary aspergillosis is a life-threatening disease occurring in patients with severe immunosuppression. It is classically associated with severe neutropenia following hematopoietic stem cell transplantation, but other risk factors include COPD, corticosteroid therapy, solid organ transplant, liver failure and preceding severe influenza infection. Due to the high mortality of the disease, rapid diagnosis and treatment are crucial. Diagnosis is based on CT scan and bronchoscopy including microscopy, culture and galactomannan detection in BAL. Histopathology remains the gold standard diagnosis but is not feasible in many cases. First line treatment is voriconazole, new recommendations also support the triazole isavuconazole.
Keywords: Aspergillose; Immunsuppression; Aspergillus spp.; COPD; Steroidtherapie; Neutropenie; Intensivstation; Isavuconazol